WAYS TO INCREASE LOCAL BUDGET REVENUES - Khurshid Khudoykulov (International Journal of Economic Integration and Regional Competitiveness, 2024)
This article outlines theoretical and scientific views on increasing the efficiency of local budget revenues. Also, based on data from recent years, local budget revenues were analyzed by region. In particular, a study was conducted to analyze tax revenues of the local budget. In particular, scientifically and practically substantiated proposals and recommendations have been developed to improve the efficiency of local budget revenues